Quartz crystal microbalance (QCM) study of electrochemical CO2 reduction on Sn electrocatalysts - Saad, Mohammed A.H.S. (2025)
The extenuation of CO2 emissions using electrochemical CO2 reduction (ECR) is a promising approach. Electrochemical routes offer a number of benefits, including customizable layout, precise product modification, mild operational temperatures, and the ability to combine CO2 reduction with the production of renewable electricity. Nevertheless, the essential technique for reprocessing CO2 as a renewable resource is electrochemical CO2 reduction, yet CO2 adsorption/reduction on catalyst surfaces is challenging. To address these concerns, Mn3O4 and Sn were produced in this work at room temperature via an electrodeposition technique, which was combined with a quartz crystal microbalance (QCM) sensor suitable for room-temperature monitoring of ECR. QCM is a compelling technique for closely inspecting the responses of CO2 reduction in real time under various applied conditions. QCM was used for the first time to study the effects of Sn electrocatalysts for ECR research, and revealed the CO2 adsorption/reduction capabilities of diverse Sn catalysts. A broad investigation showed the CO2 reduction detecting ability of Sn coated QCM sensors at room temperature. The final results revealed that Sn catalysts' capacity to reduce CO2 was evident both with and without CO2 present in the solution of sodium bicarbonate electrolyte. For all the appropriate conditions, the effect of CO2 saturated electrolyte solution on the frequency and mass change with time along with applied potential were discussed in detail.